Individuação e distinções em J. Duns Scotus - Alt, Guido José Rey (2018)
The thesis’s objective is to examine the interconnected problems of the ontological status and the distinction of the principle of individuation, the principle that seeks to explain the numerical identity of individual substances, in the metaphysics of the scholastic philosopher and theologian John Duns Scotus (1255/56-1308). The following exposition seeks to argue for the soundness of Scotus’s analysis of the concepts of identity and distinction in the framework of his doctrine of the ‘formal distinction’, which grounds his overall approach to this metaphysical principle. Our interpretative purpose is also oriented on the secondary objective of examining the consistency of an important objection posed by Ockham’s Problem.